Emerging trends and future pathways: A commentary on the present state and future of residential flood insurance in Canada. Issue 4 (2nd October 2017) - Calamai, Lapo; Minano, Andrea
Abstract : Until 2015, Canada was the only G7 country where homeowners could not purchase flood insurance. Historically, when a natural disaster occurred, the federal, provincial and municipal governments were primarily responsible for compensating homeowners and rebuilding communities to pre-disaster conditions. The rising costs of extreme weather, particularly from flooding, within the last decade have placed an unexpected burden on taxpayer-funded disaster relief programs. In recent years, the insurance industry has been placed under a spotlight as a potential resource for managing the costs of flooding and as a mechanism for shifting this financial liability away from governments. This commentary: (1) outlines the conditions needed to achieve a sound flood risk management culture, and progress made in relation to these conditions; (2) identifies the current state of residential flood insurance and the challenges facing the property and casualty insurance industry; and (3) proposes changes in public policy that are needed in order to disaster-proof Canada's economy.